Immunohistochemical localization of d‐β‐aspartic acid in congenital and acquired middle ear cholesteatoma - Shiori Kitaya; Ryoukichi Ikeda; Jun Suzuki; Hidetoshi Oshima; Yuri Nomura; Yusuke Kusano; Nobuo Ohta; Tetsuaki Kawase; Kazue Ise; Kazuhiro Murakami; Yasuhiro Nakamura; Hironobu Sasano; et al. (Laryngoscope Investigative Otolaryngology, 2022)
Abstract Objective/Hypothesis Middle ear cholesteatoma is characterized by abnormal growth of the keratinizing squamous epithelium of the temporal bone. d‐β‐aspartic acid is the major isomer of d‐aspartic acid found in elderly tissue. We assessed the immunoreactivity to k‐β‐aspartic acid of congenital and acquired middle ear cholesteatomas. Study Design Case–control studies. Material and Methods Tissue samples were collected from 21 patients comprising 21 ears with congenital middle ear cholesteatoma and 26 patients comprising 29 ears with acquired type. Their clinical and histopathological features were investigated. We divided the middle ear cholesteatoma samples into three layers: the perimatrix, matrix, and cystic contents. The patterns of immunoreactivity to d‐β‐aspartic acid expression were then assessed immunohistochemically. Results Two patterns of immunoreactivity to d‐β‐aspartic acid were detected in middle ear cholesteatoma: infiltrative and diffuse. In congenital middle ear cholesteatoma, d‐β‐aspartic acid expression was observed throughout all the layers (perimatrix, matrix, and cystic contents), and immunoreactivity to d‐β‐aspartic acid was dramatically strong in all layers. The expression levels of d‐β‐aspartic acid to the cystic content and perimatrix were significantly higher in congenital middle ear cholesteatoma than in the acquired type. Conclusions This study showed the expression levels of d‐β‐aspartic acid in middle ear cholesteatoma to differ significantly between congenital and acquired middle ear cholesteatoma. Our results indicate that overexpression of d‐β‐aspartic acid is likely to be involved in the pathogenesis of cholesteatoma, and we speculate that d‐β‐aspartic acid could be a novel biomarker for, and a therapeutic target in, congenital and acquired middle ear cholesteatoma. Level of Evidence 4